The Social Construction and Cultural Values of Nyadran Tradition in Semarang: A Case Study in Kyai Asy'ari Sentono Village - Supriyatna, Hendi; Arsal, Triwaty; Alimi, Moh Yasir (International Journal of Education and Humanities, 2025)
Local wisdom is deeply embedded in various regions, including Semarang City. However, many forms of this wisdom remain unpublished despite their unique characteristics and cultural significance. Research from the 2018 Intangible Cultural Heritage (ICH) UNESCO convention identified traditions such as the Dugderan and Warag Ngendog, offerings at Rewanda Cave Kreo in Gunung Pati sub-district, and the Bende Nangkasawit carnival. However, lesser-known traditions persist, such as Nyadran in Kyai Asy'ari Sentono village, Ngijo sub-district, where dozens of goats are ritually slaughtered. This study aims to analyze the meaning of Nyadran, examine its social construction using Peter L. Berger's theory, and explore the values represented within the tradition. The research employs a qualitative approach with data collected through interviews, observation, and documentation. The findings reveal three key aspects: First, the Nyadran tradition symbolizes gratitude, spiritual reflection, and devotion to Islamic teachings. Second, the social construction of Nyadran follows Berger's stages of externalization, objectivation, and internalization, solidifying it as an annual community tradition without empirical foundations. Third, the tradition reflects significant cultural and economic values, fostering communal solidarity while supporting local economic activities. Despite its importance, Nyadran remains underrecognized. Therefore, it is recommended that stakeholders, including cultural organizations and local governments, document, preserve, and promote this tradition to ensure its sustainability and broader appreciation. By highlighting the cultural richness of Nyadran, its values can contribute to strengthening both local identity and tourism in Semarang City